2020
DOI: 10.1177/0021998320978290
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, morphological and mechanical properties of composites based on polyamide 6 with cellulose, silica and their hybrids from rice husk

Abstract: The use of cellulosic fibers from different natural sources as fillers in polymer matrices to improve their properties has been extensively studied in the last years. It is mainly due to the vast availability of natural fibers as well as their biodegradability. The purpose of this present work was to extract cellulose, silica, and cellulose-silica fillers – these last called “hybrids” – from rice husk through delignification and subsequent oxidation and, then, prepare composites with polyamide 6 and improve ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
4
0
5
Order By: Relevance
“…However, it was suggested that there was no mass loss of silica in this range of temperature. [ 49 ] In addition to the solid residue at the 810°C was nearly 96 wt.%, the endothermic peak observed at 773°C in the DTA curve is thought to belong to the characteristic crystal silica peak caused by the calcination process at 800°C. [ 44 ] Accordingly, these crystal silica peaks were confirmed by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was suggested that there was no mass loss of silica in this range of temperature. [ 49 ] In addition to the solid residue at the 810°C was nearly 96 wt.%, the endothermic peak observed at 773°C in the DTA curve is thought to belong to the characteristic crystal silica peak caused by the calcination process at 800°C. [ 44 ] Accordingly, these crystal silica peaks were confirmed by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…The viscoelastic behaviors of PA6 and PA6-nanocomposites are shown in Figure 3 . The α-relaxation peak assigned as the tan δ peak (≈65 °C) is related to the breaking of hydrogen bonds between the polymer chains, inducing chain motion in the amorphous region [ 30 ]. The storage modulus ( E′ ) of PA6 and its nanocomposites remain at a similar level, while the tan δ peak moves to a higher temperature (from 61 to 69 °C) with the addition of NC, indicating an interaction between PA6 and NC.…”
Section: Resultsmentioning
confidence: 99%
“…1 wt% hemicellulose, 12.2 wt% lignin, and 7.9 wt% ash obtained by Zuluaga et al 20 Both results are comparing with the reported by other researchers that obtained cellulose of agro-based such as coconut (36-43 wt%), 21 wheat straw (39 wt%), 22 and Rice husk (25-35 wt%). 23…”
Section: Chemical Composition Analysesmentioning
confidence: 99%